Development of a psycho-educational anti-doping intervention program for emerging athletes - Jalleh, Geoffrey; Donovan, R.; Gucciardi, Daniel School of Physiotherapy and Exercise Science 240728E (Elsevier Australia, 2012)
Introduction: Current anti-doping programs focus on knowledge of banned substances, reporting and testing requirements, and penalties for noncompliance. This current approach ignores personality variables that may render an athlete susceptible to doping. We sought to develop an intervention targeting junior elite athletes that involved psycho-educational activities and exercises that target the personality variables we found to significantly differentiate athletes with respect to increased doping susceptibility: Sport motivation–susceptibles are more externally regulated and lesser intrinsically motivated; Achievement goals–susceptibles are characterised by lesser performance-approach and greater performance-avoidance; Athletic identity–susceptibles tend to have a strong public identity; Perfectionism–susceptibles are more concerned with mistakes and parental pressure; Fear of failure; Self-presentational concerns–susceptibles tend to be more worried about appearing athletically untalented, physically unattractive, fatigued/lacking energy, and mentally weak; Morality–susceptibles tend to have a positive disposition towards cheating and gamesmanship. Methods: The project consisted of three phases: 1) Focus group interviews with sports psychologists from across Australia to assist in generating the content of a psycho-educational intervention; 2) Following the input from psychologists a number of counselling approaches in common use by both psychologists in general and sports psychologists were reviewed to develop the specific content of the intervention; and 3) Feedback on the draft intervention was obtained from sport psychologists previously involved in the project.Results: A four modules intervention, to be delivered by a sports psychologist over four weeks in sessions lasting from 1Ω to 2 hours for groups of around 10 athletes, was developed. The intervention is titled “Improving performance by dealing with negative thoughts that can impede sport performance”. The overall aim of the intervention is to show athletes how they can overcome various negative thoughts and feelings that are impeding their performance. Discussion: By dealing with these issues, the intervention not only aims to improve performance, but also lessen athletes’ likelihood of showing poor sportsmanship, being tempted to cheat, and hence lessen their vulnerability to trying illegal methods to improve their performance. Sports psychologists who wish to field test the intervention are advised that: a) specific examples are to be elicited from athletes and from the participants’ fields of sport; b) sport psychologists could adapt their preferred counselling technique to the issues; and c) to avoid boredom and to enhance internalisation of the concepts, the sessions should be as interactive as possible.